THE CREATIVE PROCESS OF ENAROTALI DREAMS, A SCREENPLAY - Dionisius Andrew W.; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2015)
This paper is about a project on a screenplay. In my screenplay, I talk about a girl from Java who has to work in remote area in Papua Island. The girl is a volunteer teacher who has to survive to teach the students who are very different from students in Java. To develop the screenplay, I used two theories, namely culture shock and maturation. I use these two theories because in the main character experiences culture shock and maturation whe she does her voluntary teaching in Papua. To collect data, I use survey to Eranotali, Papua and libary research on Papua and its cultures. I find the theories and survey as well as libary research help me during the creative process. The theories help me develop realistic characters; while the survey and library research help me picture Eranotali as realistic as possible. I believe that when the screenplay is made into film, the audience will get the feel of Enarotali and ‘experience’ the main character’s jurney